A Front‐Illuminated Nanostructured Transparent BiVO4 Photoanode for >2% Efficient Water Splitting. Issue 2 (24th November 2015) - Kuang, Yongbo; Jia, Qingxin; Nishiyama, Hiroshi; Yamada, Taro; Kudo, Akihiko; Domen, Kazunari
Abstract : Appropriate nanostructuring and morphology control significantly improves front illumination performance and optical properties of a transparent BiVO4 photoanode, with a record high charge separation efficiency at 0.6 V versus the reversible hydrogen electrode. The obtained nanoworm electrode shows similar charge separation efficiency under both front and back illumination. With the addition of a highly active NiFe bimetallic cocatalyst, solar conversion efficiency of 2.25% is achieved.